2009년도 주요 재정사업(목재소득) 성과평가 및 모니터링 - 석현덕 (한국농촌경제연구원, 2009)
Self-Assessment of Budgetary Program(SABP) in the Korean public sector is a program in which government departments evaluate their own budgetary program(BP) by themselves. In order to perform the objective assessment, one of the most important tasks is to establish performance indicator(PI)s and to reasonably set up target values. In the case of Korea Forest Service, however, PIs have several problems such as the less rationality of performance indicators, the insufficient correlation between goals and indicators, and the irrelevance of target values. The purpose of this study is to set up the PIs and to draw the problems of BPs through monitoring activities. The scope of the study is limited to the three BPs; Support program for Using and Processing lumbers(ProgramⅠ), program for Improving the Forest products' Distribution Structures(ProgramⅡ), and program for Disaster Recoveries in Forest(ProgramⅢ). Establishing PIs was done through the step-by-step analysis, and monitoring activities were performed based on these PIs. The results show the alternative PIs to each BP, a lumber supply self-sufficiency rate in ProgramⅠ, the amount of sales in the distribution center in ProgramⅡ, and the rate to comeback to the forest management in ProgramⅢ were presented as the representative PIs. Also, the several problems of Budgetary Programs is drawn out through monitoring activities. ProgramⅠ needs to set up the specific guidelines for the construction of the facility to coincide with their original goal. ProgramⅡ is required to allocate the budget to the purpose and to make this budget focus on several key areas. Moreover, ProgramⅢ is needed to create the specific guidelines to calculate the damage ratio. Finally, we expect that most of the revealed problems are being corrected through the feedback processes of the government and that each BP can be performed better.